High‑status individuals are held to higher ethical standards [dataset] - Trautmann, Stefan T.; Wang, Xianghong; Wang, Yijie; Xu, Yilong (Universität, 2023)
Although there is evidence for the generosity of high‑status individuals, there seems to be a strong perception that the elites are selfish and contribute little to others’ welfare, and even less so than poorer people. We argue that this perception may derive from a gap between normative and empirical expectations regarding the behavior of the elites. Using large‑scale survey experiments, we show that high‑status individuals are held to higher ethical standards in both the US and China, and that there is a strong income gradient in normatively expected generosity. We also present evidence for a gap between people’s normative expectations of how the rich should behave, and their empirical expectations of how they actually do: empirical expectations are generally lower than both normative expectations and actual giving.